There is no need to talk about this : poetic inquiry from the art therapy studio - Wallace, Karen O. (Transgressions (Rotterdam, Netherlands), 2015)
The mystery of Art Therapy is demystified in this book as the author offers an illuminating glimpse into her therapy practice. The author is deeply immersed in her own creative process and the respect, delicacy, and understanding that she provides her clients shines through. The poems embrace the painful aspects of her clients lives and show how by working skillfully and creatively with trauma, abuse and mental illness, her clients move forward into joy, well-being and wholeness. Her poetic reflections move us to appreciate how art can be used as an instrument of transformation by travelling through landscapes where words cannot go. Art is unique in its ability to embrace and communicate complex, deep, and subtle aspects of emotional experience. And often the best way to reflect upon and understand these artistic processes is to respond to them with more, in the same medium or a different one. Karen Wallace convincingly does both in There Is No Need to Talk about This: Poetic Inquiry from the Art Therapy Studio. Artistic expressions and images are apt to be a few steps ahead of the analytic minds way of sorting things out. As an art therapist, she responds to visual imagery and studio environment by writing poems. Aligned with how perception and sensibility work, this language arguably offers a fuller sense of multifaceted processes of arts therapy than conventional clinical narratives. Poems hold contradictions, pare down excess verbiage, distill seeds, and speak/The thoughts of humanness that mattered. This book will help therapists and researchers gain a more complete comprehension of their work and do something creative and life enhancing with the feelings it generates in them living the process themselves as the most reliable way to bring it to others. Shaun McNiff is Lesley Universitys first University Professor and author of many books including Imagination in Action: Secrets for Unleashing Creative Expression and Art as Research Karen Wallaces There Is No Need to Talk about This: Poetic Inquiry from the Art Therapy Studio is a profoundly moving work, therapeutic, evocative, wise, tender, feeling. It is painfully evocative in its words and imagery. There are lessons here for any reader who has ever had to look deeply into the darkness that lurks beneath the traumas of daily life. Karen Wallace teaches all of how to heal, how to love, how to move forward with dignity, and courage. Norman Denzin, Professor Emeritus of Sociology, University of Illinois at Urbana-Champaign, Editor of Qualitative Inquiry and International Review of Qualitative Research Our son Connor has autism and he saw Karen Wallace for art therapy for several years as a teen. Once he said, Karen is the only one who understands me. She worked through many issues with him and helped us as parents decode his obsession with monsters. This book provides a glimpse into the genuine caring that Karen Wallace feels for every client lucky enough to see her. Kellie Garrett, ACC, MC, ICD. D, Speaker ~ Coach ~ Strategist.